M&A announcements on stock returns: evidence from private takeovers in Latin America - Morales, Lucas Vilela (2019)
This master thesis aims to analyze the impact of private takeovers announcements on acquires’ stock prices in Latin American countries, such as Brazil, Mexico, Chile, Argentina, Colombia and Peru. I gathered data from 161 M&A transactions and stock prices from 1999 to 2019 in order to test whether M&A announcements generate abnormal returns for acquiring companies in these countries as well as for the aggregate sample. I found evidence of significant and positive post-event returns for acquiring firms in Brazil, Mexico, Argentina, Chile and for the aggregate Latin America sample. Also, shareholder value creation tends to be stronger for transactions in which the target size increases relative to the acquirer. Furthermore, I found evidence of both cash and equity-financed acquisitions as being value creating for shareholders around the announcement date. Only cash deals provide significant positive abnormal returns for longer periods, though. Finally, I found evidence that both horizontal and vertical deals generate positive abnormal returns whereas there was no evidence of such effect for diversification acquisitions. This study is relevant for common shareholders, board of directors, senior management teams, investment banks, global fund managers, equity analysts, brokers as well as financial regulators. The present research contributes to corporate restructuring as well as market efficiency literature, especially for emerging and developing markets.